Estudo in vitro e in vivo da atividade Leishmanicida do extrato acetato de etila de Plectranthus amboinicus (Lour.) Spreng. frente à Leishmania (Viannia) braziliensis - Gonçalves, Thially Braga (2017)
Cutaneous leishmaniasis are anthropozoonoses caused by protozoa of the Leishmania genus. Leishmania braziliensis is most popular specie in Brazil. Plectranthus amboinicus, popularly known in Brazil as “malvarisco”, belongs to the family Lamiaceae. It has a great economic importance because of its widely medicinal use. In this work, the in vitro and in vivo effect of the ethyl acetate extracted of Plectranthus amboinicus (EAEPA) on L. braziliensis infection has been evaluated. The extracts of hexane, dichloromethane and ethyl acetate of P. amboinicus were initially tested in vitro for activity against Leishmania promastigotes. Since the EAEPA has shown the inhibition of 98.5% promastigotes at the concentration 4mg/mL, it was selected for the in vivo assays. To evaluate the effect against amastigote forms, murine intraperitoneal macrophages were infected or not with L. braziliensis and treated with different concentrations of EAEPA for 24h. Cytotoxicity, parasite load, and cytokine production have been analyzed. For the in vivo assay, Hamsters (Mesocricetus auratus; n = 20) were infected with 106 promastigotes and BALB/c mices (n = 15) with 107 of L. braziliensis on the right paw cushion and on the right ear, respectively. After the appearance of the lesions, the Hamsters were divided in 4 groups that received the following treatments: DMS0 1%; Antimony (20mg / kg / day, IM, 30 days); EAEPA (4mg / kg I.P. and I.L., 30 days). The BALB/c mice were divided into three groups: DMSO 1%, Antimony (20mg / kg / day, IM, 15 days), EAEPA (250mg / kg / day, PI, 15 days). Afterwards, the lesion thickness and parasite load have been evaluated and histopathological analyses have been done. Phytochemical analysis of EAEPA revealed the presence of flavonoids, digitalis glycosides, tannins and steroids. In vitro results have presented that EAEPA exhibited cytotoxicity from the 0.125 mg / mL concentration with 43% inhibition of cell growth. Treatment with EAEPA in vitro has presented a significant reduction of parasite load from the 0.03 mg/mL concentration. In cells treated with EAEPA, increased levels of TNF-α and IL-10, maintenance of TGF-β levels, and decreased IL-4 production have been observed. In vivo experiments, EAEPA administered intraperitoneally efficiently reduced lesion thickness, parasite load, and inflammatory parameters in Hamsters and BALB/c mice, compared to the untreated control. In summary, EAEPA was able to induce control of the lesion in the animals infected with L. braziliensis. It suggests that this may occur because the reduction of parasitic load, such as through immunoregulation of the inflammatory process. The leishmanicidal action of Plectranthus amboinicus elucidated in this work through the treatment in two animal models of infection by Leishmania braziliensis opens possibilities for the development of a new herbal medicine capable of reducing parasitemia or even cure, with low toxicity and few adverse effects.